Understanding the variation in MBA students’ experiences of using Learning Technology in Pakistan - Timsal, Ahmad; Hodgson, Vivien; Shah, Uzair (Proceedings of the International Conference on Networked Learning, 2018)
Today, technology is increasingly being viewed as a key resource for enabling innovation within teaching and learning approaches. Social media platforms and applications such as Facebook and Twitter, WhatsApp, Skype and Viber have emerged as one of the most popular mechanisms for developing the social perspective in learning. Some recent studies even refer to this phenomenon as the development of a ‘parallel infrastructure’ to institutional offerings such as Moodle. However, when any artefact (such as technology), is introduced into a learning environment, there is a possibility that it will be responded to and utilised in different ways. This paper presents the initial analysis from MBA students’ experiences of using learning technology within their studies in a Pakistani business school, to see if technology has any impact on the learning approaches, in terms of the way and the purpose for which it is being used. Phenomenographic analysis revealed some initial categories of description, which include ‘access to learning materials and other information sources’, ‘organisation of course-related activities’, ‘improved communication and connectivity’, ‘developing cooperation and collaboration’ and ‘means of overcoming socio-cultural barriers’. The degree of variation within these categories can be related to the established concepts of deep and surface level approach. For example, there were students who preferred to use technology ‘as and when required’ by their teachers, and within the same environment there were others, who appeared to take a ’deep level’ approach that involved some critical thinking about the use of technology and its subsequent influence on learning approaches. Our analysis highlights that students in relatively less developed regions are also making efforts to change themselves from ‘passive recipients’ of knowledge to active participants, who can support the learning activities of each other, using diverse forms of technology. We argue that while students may be developing an ‘alternative or parallel infrastructure to their institutional offerings’, there is no disconnect between them. It is this blend in using different forms of technology, which is encouraging the students to develop ‘informal networks’ among themselves – in an environment, which is majorly instructor-led. However, for addressing a possible ’dis(connect)’ in students’ use of various forms of technology, there is still a need for educators to ‘temper’ the enthusiasm of students, to develop a better understanding of how they should interact with technology, as this may provide some new insights for networked learning.